Propriedades mecânicas, físico-químicas e biológica de adesivo experimental com incorporação de epigalocatequina-3-galato - Fonseca, Beatriz Maria da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate the effect of EGCG in an experimental adhesive to reduce the hybrid layer degradation, through mechanical, physical-chemical and biological analysis. The first step of this study involved manipulation of the adhesive model with the incorporation three different concentrations of EGCG (0.5%, 1.0% and 1.5%) in relation BisGMA 55% / 45% HEMA, 0.5% camphorquinone and 0.5% DMAEMA. The conversion degree (DC) of adhesive monomers was evaluated by micro-Raman spectroscopy (GC: EGCG 1.5 (1.5%) - 99,11a; EGCG 1.0 (1.0%) - 99,02a; EGCG 0.5 (0.5%) - 96,58ab; Control - 85,47b). The second step involved the mechanical and physicochemical analysis [flexural strength (FS) and elastic modulus (EM); resiliency modulus (RM) and compressive bond strength (CBS), sorption (A) and solubility (S) in water; shrinkage polymerization (SP)]; microtensile bond strength test (μTBS) immediately (24 h) and longitudinal (6 months) and biological analyze [cytotoxicity assay (CY)]. The results were: FS, EM, RM, CBS and SP showed no significant difference between groups; A and S tests showed reduced values only for EGCG 0.5 and 1.0 groups. RA immediately (24) did not differ between groups. After six months there was a reduction of the values only for the control and EGCG 1.5 groups, EGCG groups 0.5 and 1.0 maintained the RA values. CY: EGCG incorporation increased the cell viability in 0.1% and 1.0% dilutions compared to the control group. It was concluded incorporation of EGCG at 0.5, 1.0 and 1.5 concentrations did not affect the degree of conversion of the monomers. Thus, the incorporation of 0.5% (100 μg/ml) and 1.0% (200 μg/ml) EGCG amount can preserve the hybrid layer formed and prolong longevity composite resin restorations in addition to increasing cell viability.

O objetivo desse estudo foi avaliar o efeito da adição de EGCG em adesivo experimental na manutenção da camada híbrida, avaliando suas propriedades mecânicas, físico-químicas e biológica. A primeira etapa do estudo envolveu a manipulação do adesivo com incorporação de EGCG (0,5%, 1,0% e 1,5%) na relação BisGMA 55% / HEMA 45%, canforoquinona 0,5% e DMAEMA 0,5%. O grau de conversão (GC) dos monômeros foi avaliado por Espectroscopia micro-Raman (GC : EGCG 1.5 - 99,11a; EGCG 1.0 - 99,02a; EGCG 0.5 - 96,58ab; Controle - 85,47b). A segunda etapa envolveu a realização de análises mecânicas e físico-químicas [resistência flexural (RF) e módulo de elasticidade (ME); módulo de resiliência (RE) e resistência a compressão(RCo); sorção (A) e solubilidade (S) em água; contração de polimerização (CP)]; teste de resistência à microtração (RA) imediato (24 h) e longitudinal (6 meses); e teste biológico [ensaio de citotoxicidade (CI)]. Os resultados foram: RF, ME, RE, RCo e CP não apresentaram diferença significativa entre os grupos. Os testes de A e S apresentaram redução dos valores para os grupos EGCG 0.5 e 1.0; RA imediato (24 h) não apresentou diferença entre os grupos. Após 6 meses houve redução dos valores somente para os grupos Controle e EGCG 1.5, os grupos EGCG 0.5 e 1.0 mantiveram os valores de RA constantes. CI: a incorporação de EGCG aumentou a viabilidade celular nas diluições de 0,1% e 1,0%, comparado ao grupo Controle. Pôde-se concluir que a incorporação de EGCG independente da concentração não afetou o GC. As concentrações de 0,5% (100 μg/ml) e 1,0% (200 μg/ml) em volume de EGCG é capaz de preservar a camada híbrida formada e prorrogar a longevidade das restaurações em resina composta, além de aumentar a viabilidade celular
Keywords: Adesivos dentarios; Dentina; Monomeros; Resinas compostas; Dentin